How often should sitting and rising from a chair be evaluated in patients with Duchenne muscular dystrophy? - Hukuda, Michele Emy; Caromano, Fátima Aparecida; Escorcio, Renata; Carvalho, Eduardo Vital de; Blascovi-Assis, Silvana Maria; Voos, Mariana Callil (Arquivos de Neuro-Psiquiatria, 2017)
Objective To determine how often sitting/rising from a chair should be assessed in Duchenne muscular dystrophy (DMD) patients to avoid redundant/missing data.Methods Sitting/rising from a chair was evaluated in 26 DMD children (5-12 yrs), in three-month intervals, over twelve months, with the Functional Evaluation Scale (domain sitting/rising from a chair). Scores were compared by effect sizes (ES) and standardized response means (SRM) (responsiveness analysis).Results Sit-to-stand showed low-to-moderate responsiveness in three-month intervals (ES:0.23-0.32; SRM:0.36-0.68), moderate-to-high responsiveness in six-month intervals (ES:0.52-0.65; SRM:0.76-1.28), high responsiveness at nine-month (ES:0.84-0.91; SRM:1.26-1.64) and twelve-month intervals (ES:1.27; SRM:1.48). Stand-to-sit showed low responsiveness in three-month intervals (ES:0.26-0.49; SRM:0.37-0.42), moderate responsiveness in six-month intervals (ES:0.50-0.78; SRM:0.56-0.71), high responsiveness in nine-month (ES:0.94-1.00; SRM:0.84-1.02) and twelve-month intervals (ES:1.13; SRM:1.52).Conclusion Six months or longer intervals for reassessment are indicated to evaluate sitting/standing from a chair in DMD patients.
Keywords: muscular dystrophy, Duchenne; motor activity; task performance and analysis; outcome assessment (health care; physical examination